Permanent magnet machine based starter-generator system with modulated model predictive control - Yeoh, Seang Shen; Yang, Tao; Tariscotti, Luca; Hill, Christopher Ian; Bozhko, Serhiy; Zanchetta, Pericle (Institute of Electrical and Electronics Engineers, 2017)
The paper describes a hybrid control scheme for a permanent magnet machine based starter-generator (S/G) system. There has been increased usage of electric drive systems in the transportation sector for increased efficiency and reduced emissions. One of the advantages of utilising suitable electric drives is the capability to operate as a starter or generator. The control design of such a system should be considered due to the operating requirements and fast load changes. Different control approaches should therefore be considered in order to achieve these goals, which are a current trend in the transportation sector. Model Predictive Control (MPC) is considered due to its very fast dynamic performance. In particular, Modulated Model Predictive Control (M²PC) was recently introduced and showed significantly better performance than the standard MPC. The control scheme used in this paper utilises M²PC for the current inner loop and PI controllers for the outer loop. The use of M²PC allows very fast transient current response for the S/G system. The proposed overall control benefits from reduced current ripple when compared with a full cascaded PI control scheme. Simulation analyses and experimental results show the capability and performance of the designed controller across both starter and generator modes.